MODERNISASI PENDIDIKAN ISLAM INDONESIA: PENGALAMAN AL-JAM’IYATUL WASHLIYAH - Munzir Munzir (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2021)
This simple article discusses Modernization of Indonesian Islamic Education: The Experience of Al-Jam'iyatul Washliyah, with sub-discussions, namely as follows: a. Philosophy and Typology of Reform; b. Aspects of Modernization of Education: objectives, curriculum, methods, human resources; institutional; c. Contribution and Influence (Al Washliyah Education Statistics on National Education). Al-Jam'iyatul Washliyah, in the world of education, one of these large organizations also has a lot of influence and plays a role in the world of education, especially in North Sumatra from kindergarten / RA education to higher education which is known in the field as UNIVA or Al-Washliyah University or also known as UMN (University of the Muslim Archipelago). Al-Jam'iyatul Washliyah held many reforms in education regarding aspects of objectives, curriculum, methods, human resources and institutions. Contribution and Influence (Al Washliyah Education Statistics on National Education). With Al-Jam'iyatul Washliyah in the modernization of education, this college also contributes a lot to national education.